ANALISIS SISTEM DAN PROSEDUR PENYUSUNAN ANGGARAN PENDAPATAN DAN BELANJA DESA DI DESA KEMBES SATU KECAMATAN TOMBULU KABUPATEN MINAHASA - Soeradi, Dewi Shinta; Tinangon, Jantje J.; Afandi, Dhullo (Universitas Sam Ratulangi, 2018)
This research aims to find out and describe about the system and procedure of drafting the Village Budget Kembes Satu Village Tombulu Sub-District Minahasa Regency. The concept of system and procedure used in this research is Standard Operational Procedure and COSO. While the research method used is the qualitative method where the researcher conducts data collection through interview. This research attempts to investigate whether the system and procedure of drafting the Village Budget Kembes Satu Village is in accordance to the regulation Permendagri No. 113 Year 2014.One of the findings of this research is that part of the draft has been done according to the system and procedure, which is included in the ministerial regulation Permendagri No. 113 Year 2014.Keywords: System and Procedure, Village Budget, Permendagri No. 113 Year 2014